2016
DOI: 10.5606/kbbihtisas.2016.62444
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on nasal packing after septoplasty: does it matter in terms of patient comfort, bleeding, and crust or synechia formation?

Abstract: Nasal packs can be more useful in patients who suffer from bleeding-related morbidity, while septoplasty applied without nasal packs can be more suitable in patients with obstructive sleep apnea. The use of nasal packs in septoplasty should be determined on an individualized basis with respect to the characteristics of each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
8
0
3
Order By: Relevance
“…Figure shows the flow chart of the search results. Of the 281 studies identified, 20 studies met our criteria for thorough review …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure shows the flow chart of the search results. Of the 281 studies identified, 20 studies met our criteria for thorough review …”
Section: Resultsmentioning
confidence: 99%
“…Many different packing materials have been invented and used to prevent complications of septoplasty such as bleeding, synechia, septal hematoma, and infection. There have been several meta‐analyses examining the efficacy of nasal packing after septoplasty . Certal et al discussed the transseptal suturing technique compared to nonabsorbable packing method.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study undertaken by Koc et al in 2016 (18), the problems such as pain, bleeding, nasal obstruction, mucosal synechia and anesthesia complications were examined in the patients with and without nasal packing during the first week after septoplasty. The results revealed less bleeding and nasal obstruction in the patients without nasal packing and more pain and discharge in packing group.…”
Section: Discussionmentioning
confidence: 99%